A publicação mediata das decisões judiciais do Tribunal de Justiça do Tocantins e seu uso instrumental como ação comunicativa - Lopes, Gizella Magalhães Bezerra Moraes (Universidade Federal do Tocantins, 2022)
This paper aims to analyze the mediate publicity of judicial decisions as an instrument of institutional communication of a state power – the judiciary – its principles and its use in the context of legitimation, validity and guarantee of rights. It addressed the concept of mediate advertising and social communication within the scope of public communication and the current insertion in the positive order as a fundamental right. Considering the constitutional jurisdiction to which the Brazilian State is subject, as well as the republican model of balance of powers that shape recent democracy in the country, it is the State's duty to promote spaces that guarantee the improvement of the structural bases of the democratic rule of law. For this, we highlight in this research, the role of justice communication in promoting this locus for the improvement of the public sphere in an interdisciplinary dialogue bias. This, at the same time that it favors the validity of the right, amplifies the result of the actions of justice, in addition to collaborating as an instrument for the maturation of this space that wants to be more deliberative. The research is based on bibliography and institutional actions that converge to the theme. It was found that the justice system is a recurrent thematic agenda in institutional communication actions of the judiciary and, therefore, a favorable space for a process of improvement of the public sphere in the Habermasian perspective, as the use of the judicial decision as a communicative action it is invariably echoed by other media for providing information of public interest. Finally, the final considerations point to the real need in this mass media society to ensure that the publicity of court decisions is treated by institutional communication instruments that, based on the fundamental principle of the right to communication, serve, within its structures of power, to guarantee rights, from the collaborative construction of contents in institutional communicative action. Therefore, as an interdisciplinary propositional work of a professional master's degree, in the end, it is proposed the construction of a tool in the TJTO's electronic judicial process, aiming to amplify the communicative action of this state power structure.